2016
DOI: 10.1590/1519-6984.18314
|View full text |Cite
|
Sign up to set email alerts
|

Benthic microalgae community response to flooding in a tropical salt flat

Abstract: This research evaluated the effect of flooding on the microphytobenthos community structure in a microbial mat from a tropical salt flat. Field samples were collected during four consecutive days: on the first three days the salt flat was dry, on the fourth day it was flooded by rain. In order to evaluate the community maintained in flood conditions, samples from this area were collected and kept in the laboratory for 10 days with sea water. The results of total abundance of microphytobenthos varied from 4.2 ×… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
1
1
Order By: Relevance
“…In comparison with other studies, densities were obtained which were 100 times lower than those found in Venice Lagoon in Italy (Facca et al, 2002) and in a saline wetland dominated by cyanobacteria in Rio de Janeiro, Brazil (Masuda and Enrich-Prast, 2016). In the case of the Caribbean Sea, comparisons cannot be made with other studies, since the few that calculated density associated it with macroalgae or marine phanerogam biomass, as they provide heterogeneity of space for the settlement and colonization of Epiphytes, growing the probability of increased microalgae richness and abundance.…”
Section: Discussioncontrasting
confidence: 54%
“…In comparison with other studies, densities were obtained which were 100 times lower than those found in Venice Lagoon in Italy (Facca et al, 2002) and in a saline wetland dominated by cyanobacteria in Rio de Janeiro, Brazil (Masuda and Enrich-Prast, 2016). In the case of the Caribbean Sea, comparisons cannot be made with other studies, since the few that calculated density associated it with macroalgae or marine phanerogam biomass, as they provide heterogeneity of space for the settlement and colonization of Epiphytes, growing the probability of increased microalgae richness and abundance.…”
Section: Discussioncontrasting
confidence: 54%
“…Similarly, continuously fluctuating salinity in the intertidal mangrove ecosystems might exhibit the migration of cyanobacteria with inundation with ebb tides. The community composition of cyanobacterial assemblages is influenced by the salinity (Masuda & Enrich-Prast, 2016). The prominence of heterocyte cyanobacteria are observed in less saline conditions, however, increased salt content favoured the growth of non-heterocyst genera (Srivastava et al, 2009).…”
Section: Discussionmentioning
confidence: 99%